2018
DOI: 10.1177/0309132518817824
|View full text |Cite
|
Sign up to set email alerts
|

Geographies of public space: Variegated publicness, variegated epistemologies

Abstract: Given the rapid diversification and mutation of public space and public life across the globe, this article theorises epistemologies of publicness that move the research agenda beyond the conceptual straitjacket of presence, accessibility and visibility. It develops three theoretical approaches: public space as situated and lived; public space as assemblage; and public space as a liminal zone between inclusion and exclusion. Signposting more open-ended, flexible, processual, performative and ambivalent concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 133 publications
0
51
0
2
Order By: Relevance
“…We highlight the importance of these activity places (especially workplaces and parks and green spaces) because ignoring people's exposures in these activity places will highly likely lead to erroneous results in the measurement of ethnic exposure and racial/ethnic segregation. As recent studies suggest, workplaces [36] and open spaces [37] are other areas beyond people's residential neighborhoods that are important for examining socio-spatial segregation or integration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We highlight the importance of these activity places (especially workplaces and parks and green spaces) because ignoring people's exposures in these activity places will highly likely lead to erroneous results in the measurement of ethnic exposure and racial/ethnic segregation. As recent studies suggest, workplaces [36] and open spaces [37] are other areas beyond people's residential neighborhoods that are important for examining socio-spatial segregation or integration.…”
Section: Discussionmentioning
confidence: 99%
“…As recent studies indicate, even when disadvantaged residents have high exposures to advantaged social groups, their relative isolation and segregation may persist [38]. This is because cross-group contacts or encounters in urban spaces do not necessarily translate into true social integration or respect for difference [39]; rather, spaces of encounters could remake and enact social difference, and such encounters can also expose minorities to discrimination [13,37]. It is thus important to mitigate prejudice between racial/ethnic groups in non-residential places and stigmatization that may reinforce social isolation [40].…”
Section: Discussionmentioning
confidence: 99%
“…They also observed the sentiment among native residents that migrants are ‘outsiders’ who are not equally entitled to the use of public spaces. In other words, a space of encounter can also remake and enact differences (Qian, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thinking more widely, digitally mediated forms of stranger intimacy or avoidance can be situated within a wider process of boundaryblurring in our contemporary moment taking place between conventional relations of public/private (Koch, 2020;Qian, 2018), and by association between relations such as formal/ informal work (Glucksmann, 2011;Wheeler and Glucksmann, 2014), between producers/ consumers (Bruns, 2010;Ritzler and Jurgenson, 2010) and in terms of social categories such as friend, guest, host or community member. Further, Cockayne et al (2017) have demonstrated that digital technology can also extend intimacy to the non-or more-thanhuman as people knowingly interact, for example, with robots and algorithms designed to simulate human dialogue in the pursuit of sexual pleasure and fantasy.…”
Section: Researching Stranger Intimacymentioning
confidence: 99%